PHBS BAGI ANAK PENYINTAS BENCANA DI SDN INPRES 1 DESA ROGO KECAMATAN DOLO SELATAN KABUPATEN SIGI - Arifin, Pitriani; Kiki Sanjaya; Grasela Olivia Rambi; Firmansyah (Jurusan Farmasi FMIPA Universitas Tadulako, 2022)
In 2021 there were 3,058 disasters, 42.1% were floods. One of the flood-affected areas was Rogo Village, the disaster would be followed by the emergence of refugees who were not supported by adequate sanitation facilities, this could trigger an outbreak so that knowledge of PHBS especially a childrens needs to be improved. Behavior change is not instantaneous, to accelerate the process, efforts are needed to increase knowledge and supporting facilities. The academic community of public health faculty will provide education for students at Inpres 1 Rogo Elementary in South Dolo District, Sigi Regency regarding PHBS steps that must be carried out in post-disaster conditions. This community service was carried out on 16th July 2022, starting with a pre-test to measure the participants' prior knowledge regarding PHBS and after the counseling it would end with a post-test to measure their increases of knowledge. The activity was attended by 23 students and 4 teachers. Based on the results of the pre-post test, it is known that the extension materials can increase the participants' knowledge regarding PHBS, this can be seen from the increase in the post-test scores. The highest increase in knowledge related to handwashing steps in accordance with the Ministry of Health guidelines, the value increased from 0% to 92.34%. Meanwhile, students' understanding of the requirements for â€œJajan Sehatâ€ has not been maximized even after being given education, this is illustrated by the increases scores of in participant is 21.73% to 78.26%, this it lower than the increases a scores of participants in other sections.